Music Aptitude, Training, and Cognitive Transfer: A Mini-Review - Lu Wang (Frontiers in Psychology, 2022)
In this mini-review, the genetic basis of music aptitude and the effects of music training are discussed. The review indicates that regardless of levels of innate ability, experience-induced neuroplasticity can occur as a result of music training. When that happens, it can be expressed as functional or structural brain changes. These changes are often accompanied by improvement in performance in tasks involving auditory analysis. Specifically, music training effects can transfer to a closely related cognitive domain such as auditory processing (near transfer). Music training can also affect more distantly related cognitive domains such as spatial and linguistic domains. Lastly, music training can affect general intelligence (“g”) (far transfer). Music training can mold behavioral brain development and confers cognitive benefits beyond music.